HIGH DOSE RATE BRACHYTHERAPY IN BENIGN UTERINE BLEEDING DISORDERS - KHORPRASERT, Chonlakiet; JUMPANGERN, Chotika (The ASEAN Journal of Radiology, 2023)
A case report of benign uterine bleedings (metropathia) was treated with high dose rate brachytherapy. The radiation doses were 2 fractions of 700 cGy at 1 centimeter from the tandem at four weeks interval. The patient had no bleeding in a month after treatment. She could tolerate the treatment well without any complications. High dose rate brachytherapy should be remembered in cases of uterine bleeding resisted to other therapies especially in cases of high risk for operation. However, long term follow-up should be done to evaluate late radiation effect of high dose rate radiation for benign uterine bleedings.